Alternative indicators of handpump functionality: Toward consistent performance-oriented monitoring - McManus, Catherine; Lane, Kaycie; Diarra, Samuel; Cronk, Ryan (PLOS Water, 2025)
Many people in rural Sub-Saharan Africa use a communal handpump as their primary drinking water source. Handpump performance is assessed as “functionality,” typically measured using a binary indicator of whether a pump can produce water. This indicator does not reflect service delivery goals defined by the United Nations. We used a cross-sectional dataset of 1682 handpumps from 10 Sub-Saharan African countries (Ethiopia, Ghana, Kenya, Malawi, Mali, Mozambique, Niger, Uganda, Zambia, and Zimbabwe) to explore alternative functionality indicators and potential performance standards for those indicators. Alternative functionality indicators studied here included whether a breakdown occurred in the past year and, if so, in the two weeks preceding the survey, downtime during the most recent breakdown, strokes required to produce water, the water produced per subsequent stroke, and service continuity. We conducted a factor analysis to determine the uniqueness of each of these indicators and a threshold analysis to determine the sensitivity of functionality rates (such as “X% of handpumps are functional”) to performance standards. We found that the studied indicators are unique, not redundant, and cannot be combined without an unacceptable loss of performance information. Using Monte Carlo analysis, we found that a functionality assessment using these indicators would be highly sensitive to the thresholds used to evaluate performance. This work demonstrates the importance of selecting functionality indicators to measure progress and thresholds to assess progress. The indicators explored here cannot be reduced or combined and should not be conflated, and selected thresholds may greatly impact how rural handpumps are evaluated. Handpump functionality indicators and thresholds should be selected to reflect performance goals for communal water supply. Once goals are established, indicators and contextualized thresholds can be selected to reflect those goals. Policy decisions related to handpump management should be based on assessments using indicators that reflect the intended policy outcomes.